Seasonal Assessment of Relative Humidity, Ambient Air Temperature and CO2 Concentration Level in School Buildings of Kigali-Rwanda - IRANKUNDA, Elisephane; Tuyisabyimbabazi, Dieudonne (International Journal of Sustainable Development & World Policy, 2019)
Numerous researches on air quality have shown that schools settled in poor ambient air quality regions, the later can negatively affect health of people at the school including students, teachers and other staff members. In Kigali city, most of the schools are naturally ventilated given their surroundings, school car-parks, school occupancy and number of people attending school daily. The seasonal assessment of relative humidity, ambient air temperature and co2 concentration levels in school buildings of Kigali was the main objective of this paper. This research was carried out within three schools located in different parts of Kigali city and having dissimilar construction designs. Sampling activities were performed during both dry and rainy seasons by using air visual nodes instruments. Results indicated that the level of ambient air temperature for dry season and rainy season was in the range of (21-27) oC and (18-25) oC respectively for the three schools. The carbon dioxide concentration for the schools was in the range of (350-450) ppm for dry season and (400-550) ppm for rain season. The relative humidity of rainy season was higher than that of dry season. The result values found exceeded the recommended values of World Health Organization guidelines of 18 oC for temperature and 350 ppm for CO2. This paper suggests that school-car-parks and school-kitchens should be remote from schools. Waste-materials at school should be well managed and their disposal should be away from school-location. Schools should be surrounded by trees and gardens for better air quality within schools.